Learning to Laugh - Gary McGuire (Epitome Books, 2009)
The attitude of a person measures the altitude of his or her success and happiness. Success, and and a resultant happiness, is not determined by how much you earn, or what is your status in society. It is determined by whether or not you can achieve your chosen goals in life.